Funções de reação fiscal horizontal para os estados brasileiros: há guerra fiscal no Brasil ? - Andrade, Pedro de Oliveira (2012)
The Tax on Circulation of Goods and Services (ICMS), of state competence, is the most important tax in Brazilian economy, and Brazilian states have used it as an instrument of industrial policy, giving tax incentives to attract investments. There is anecdotal evidence that states engage in horizontal tax competition, in which entities of same hierarchical level vie for a bigger share of tax revenues. In this "tax war" each state, by setting its rates, takes into account other states’ taxes. In Game Theory language, the setting of the tax rate would be the "strategy of the game”. This dissertation aims to estimate a state-level tax reaction function, with panel data for the period 1994-2008, in which the ratio ICMS Revenue/State Gross Domestic Product is used as a tax rate measure. Two different models are implemented: one in which states act simultaneously in setting rates (Nash model), and another which admits the possibility that one state acts as a Stackelberg leader by setting its rates at first; the others observe the leader and then play Nash. The results suggest a positive slope of the fiscal reaction function, consistent with the empirical literature. In the Stackelberg model, only the states of Bahia and Goiás, besides the Federal District, present statistically significant coefficients in all tested specifications.